Effects of Composite Supplement Containing Collagen Peptide and Ornithine on Skin Conditions and Plasma IGF-1 Levels—A Randomized, Double-Blind, Placebo-Controlled Trial - Ito, Naoki (Mar Drugs, 2018)
Aging-associated changes of skin conditions are a major concern for maintaining quality of life. Therefore, the improvement of skin conditions by dietary supplementation is a topic of public interest. In this study, we hypothesized that a composite supplement containing fish derived-collagen peptide and ornithine (CPO) could improve skin conditions by increasing plasma growth hormone and/or insulin-like growth factor-1 (IGF-1) levels. Twenty-two healthy Japanese participants were enrolled in an 8-week double-blind placebo-controlled pilot study. They were assigned to either a CPO group, who were supplemented with a drink containing CPO, or an identical placebo group. We examined skin conditions including elasticity and transepidermal water loss (TEWL), as well as plasma growth hormone and IGF-1 levels. Skin elasticity and TEWL were significantly improved in the CPO group compared with the placebo group. Furthermore, only the CPO group showed increased plasma IGF-1 levels after 8 weeks of supplementation compared with the baseline. Our results might suggest the novel possibility for the use of CPO to improve skin conditions by increasing plasma IGF-1 levels.